2023
DOI: 10.1007/s00167-023-07555-0
|View full text |Cite
|
Sign up to set email alerts
|

Midterm results of intra‐articular stromal vascular fraction injection for the treatment of knee osteoarthritis

Oğuzhan Çimen,
Kaan Süleyman Irgıt,
Taner Bekmezci
et al.

Abstract: Purpose This study aimed to evaluate the safety and eicacy of intra-knee stromal vascular fraction (SVF) injection in patients with symptomatic knee osteoarthritis at the midterm (3-year) follow-up. Methods SVF injection was applied to 25 knees of 20 patients. Eighteen patients (90%) were female, and the means ± standard deviations of age was 61.9 ± 7.8 (range, 50-76) years. Patients who received conservative treatment for at least 6 months and had radiographic Kellgren-Lawrence (K-L) grades 2 and 3 varus gona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In a recent publication, confirmed that the cartilage lesion size and number of SVF cells strongly influence the clinical outcome of knee OA treatment 25 . The therapeutic effects of SVF can persist for the first 2 years in patients with knee OA grades 2-3, and the positive effects of the injection disappear in the third year 26 .…”
Section: Stromal Vascular Fraction From Adipose Tissuementioning
confidence: 99%
“…In a recent publication, confirmed that the cartilage lesion size and number of SVF cells strongly influence the clinical outcome of knee OA treatment 25 . The therapeutic effects of SVF can persist for the first 2 years in patients with knee OA grades 2-3, and the positive effects of the injection disappear in the third year 26 .…”
Section: Stromal Vascular Fraction From Adipose Tissuementioning
confidence: 99%